Shallow gas cloud illumination analysis by the focal beam method - Abdul Latiff, Abdul Halim (2016)
This research will address the illumination issue of seismic data below a shallow gas cloud, also known as shallow gas accumulation. In general, poor and distorted seismic data underneath gas zones depend on four major factors; namely the velocity of the gas zones, the depth of the target reflector, the location of the source and the receiver during seismic acquisition, and the frequency of the seismic signals. These factors will be scrutinized in detail by using the focal beam method. The focal beam method incorporates the double focusing concept in order to obtain two important attributes for illumination analysis: (i) Resolution function beam, (ii) amplitude versus ray parameter (AVP) imprint, which is obtained by transforming the modelled data into the radon domain. Both illumination attributes are then applied to a gas-affected field in the Malaysia Basin. The results show well-defined illumination beneath the shallow anomalies and provide a better representation of the subsurface.